2019
DOI: 10.1111/ajd.12990
|View full text |Cite
|
Sign up to set email alerts
|

Apremilast as a new treatment option for Acrodermatitis continua of Hallopeau

Abstract: postinflammatory hyperpigmentation. The absence of vascular lesions in this case may be due to the fact that we use a nonpolarized dermoscope. However, in our second case telangiectasias and also brownish structures were observed.In conclusion, vascular structures (lacunes, vessels and reddish background) and brown dots may be dermoscopic findings of angiolymphoid hyperplasia with eosinophilia. However, these are not specific and may also be observed in various inflammatory and neoplastic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 6 publications
0
15
0
2
Order By: Relevance
“…2 Most recently, a growing number ofmostly successfultreatment experiences with biologics targeting tumor necrosis factor (TNF)-a, interleukin (IL)-17 or IL-(12)/23 and new small molecules (phosphodiesterase type 4 inhibitor) approved for plaque type psoriasis have been published. 2,7,8,[11][12][13][14][15][16][17][18][19] A recent review suggests a treatment algorithm starting with topical glucocorticoids under occlusion as first-line therapy, escalating to either cyclosporin, acitretin, adalimumab, etanercept, infliximab or ustekinumab as first-line systemic treatment, followed by systemic glucocorticoids, methotrexate or photo (chemo)therapy as second-line systemic therapies. 20 However, there is no clear recommendation which of the first-line systemic therapies to begin with.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Most recently, a growing number ofmostly successfultreatment experiences with biologics targeting tumor necrosis factor (TNF)-a, interleukin (IL)-17 or IL-(12)/23 and new small molecules (phosphodiesterase type 4 inhibitor) approved for plaque type psoriasis have been published. 2,7,8,[11][12][13][14][15][16][17][18][19] A recent review suggests a treatment algorithm starting with topical glucocorticoids under occlusion as first-line therapy, escalating to either cyclosporin, acitretin, adalimumab, etanercept, infliximab or ustekinumab as first-line systemic treatment, followed by systemic glucocorticoids, methotrexate or photo (chemo)therapy as second-line systemic therapies. 20 However, there is no clear recommendation which of the first-line systemic therapies to begin with.…”
Section: Introductionmentioning
confidence: 99%
“…42 Due to low efficacy, we do not recommend the use of fumaric acid esters or apremilast to control ACH symptoms based on our experience. For apremilast, individual case reports showed a good efficacy on ACH, 11,18,19 while therapy failure of apremilast is mentioned in other reports as ineffective prior therapy only when a positive treatment effect of another drug is described. 13,15 Our data suggests that biologics may be of use for clinicians in managing ACH as second-line treatment.…”
mentioning
confidence: 99%
“…Weight loss and depression have also been reported, but they do not usually require discontinuation of the therapy as these side effects can be solved or reduced simply by lowering the dose. There is just another case in literature of ACH successfully treated with Apremilast (Calleja‐Algarra, Aragón‐Miguel, & Velasco‐Tamariz, ). However, that patient did not reach a complete recovery as our patient did, after just 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Apremilast is a relatively safe and easily administrable agent compared with biologics; its efficacy and safety for psoriasis and palmoplantar psoriasis have also been demonstrated. 4 Very recently, Calleja Algarra et al 5 reported apremilast as a new treatment option for ACH for the first time. To the best of our knowledge, the present case is the second to be reported showing the efficacy of apremilast on ACH.…”
Section: Successful Treatment Of Acrodermatitis Continua Of Hallopeaumentioning
confidence: 99%